2022
DOI: 10.24018/ej-eng.2022.7.1.2691
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Influence of Flow Control to the Kinetic Detachment in the Near-Wake of an Ahmed Body

Abstract: Environmental pollution represents today the greatest danger to which the world has to do faces. Several activities of human are accused. Among the more devastative, the transport sector and in particular that of the car remains more to be feared. For control and to reduce the impact of the pollution of this sector on the environment, it is necessary to control the profile of the flow around the vehicle. The structure of the flow around a motor vehicle is strongly separated and swirling. It presents recirculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The work presented by Guilmineau [1] shows the computational study on the Ahmed body by employing RANS model, where the numerical results showed good agreement with the experiment except for the flow reattachment. Besides that, CFD simulation was performed on the Ahmed body to study the interaction between vortex structures and the rear window at the near wake [2].…”
Section: Introductionmentioning
confidence: 99%
“…The work presented by Guilmineau [1] shows the computational study on the Ahmed body by employing RANS model, where the numerical results showed good agreement with the experiment except for the flow reattachment. Besides that, CFD simulation was performed on the Ahmed body to study the interaction between vortex structures and the rear window at the near wake [2].…”
Section: Introductionmentioning
confidence: 99%